A systems biology-based study to assess the effects of TNF-alpha ± apigenin in triple-negative breast cancer cell line - Amjad, E; Sokouti, B; Asnaashari, S; Dastmalchi, S (Plant Science Today, 2025)
Triple-negative breast cancer (TNBC) is a type of breast cancer that lacks estrogen, progesterone, and HER2 receptors. Various treatment methods are available for breast cancer, but therapies with minimal toxic side effects are particularly important. This study computationally investigates the impact of apigenin, a compound used in traditional Chinese medicine, on the TNBC cell line. The GSE120550 dataset was retrieved from the NCBI-GEO database. BRB-ArrayTools were used for pre- and post-processing to identify significantly differentially expressed genes. Additionally, the DAVID web server was utilized to analyze three main components: "biological process," "cellular component," and "molecular function," along with the KEGG signaling pathway. Finally, a Venn diagram was employed to thoroughly investigate the number of shared genes among 15 groups derived from 6 compared sample sets. The primary analysis of 6 pairs of samples revealed significant differentially expressed genes (DEGs), which were prioritized using the TOPPgene web server. These identified genes, playing key roles in inhibiting the progression of BC, are involved in various signaling pathways. Protein-protein interaction network analysis highlighted the biomarkers associated with the inhibitory effects of apigenin across the 15 sets derived from the 6 sample pairs. The findings of this study confirm the inhibitory effects of apigenin, with no toxic side effects, on patients with TNBC. This natural compound holds promise for future therapeutics and novel drug designs.